2020
DOI: 10.4254/wjh.v12.i10.816
|View full text |Cite
|
Sign up to set email alerts
|

Increased incidence of and microbiologic changes in pyogenic liver abscesses in the Mexican population

Abstract: BACKGROUND Pyogenic liver abscess (PLA) is a rare disease with an estimated incidence that varies widely across the globe, being as high as 115.4/100000 habitants in Taiwan and as low as 1.1-1.2/100000 habitants in Europe and Canada. Even though there are multiple microorganisms capable of producing an abscess in the liver, including Entamoeba histolytica , fungi, and viruses, most abscesses are derived from bacterial infections. The epidemiology of PLA in Mexico is curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
2
1
Order By: Relevance
“…The finding that most of our patients with liver abscesses were relatively young at presentation (median age 39 years for ALA and 46 years for PLA) concurs with previous reports from our region [ 11 – 13 ]. However, it contrasts with reports from the Western hemisphere in which older age at presentation was documented [ 2 , 10 , 14 16 ]. Male preponderance was evident in our series (87.5% for ALA, 75.7% for PLA) and is consistent with similar studies from our region [ 11 – 13 ].…”
Section: Discussioncontrasting
confidence: 91%
“…The finding that most of our patients with liver abscesses were relatively young at presentation (median age 39 years for ALA and 46 years for PLA) concurs with previous reports from our region [ 11 – 13 ]. However, it contrasts with reports from the Western hemisphere in which older age at presentation was documented [ 2 , 10 , 14 16 ]. Male preponderance was evident in our series (87.5% for ALA, 75.7% for PLA) and is consistent with similar studies from our region [ 11 – 13 ].…”
Section: Discussioncontrasting
confidence: 91%
“…34 The results of this study revealed that 13.9% of the patients suffered from septic shock, which is consistent with previous reports. [35][36][37] There has been no significant change in the incidence of septic shock over several years. Multivariate analysis identified coexisting DM and gas formation as risk factors for septic shock in PLA patients.…”
mentioning
confidence: 99%
“…The incidence of PLA is higher in Asia compared to Europe and the United States, with an annual incidence of 1.1−5.4/100,000 in China 3 , 4 and up to 17.6/100,000 in Taiwan, and 1.0−4.1/100,000 in European countries and America. 5 , 6 , 7 Due to the rapid advances in medical technology, the diagnosis and treatment of PLA have greatly improved, resulting in a decrease in mortality rates from >80% at the beginning of the previous century to <10%. 8 , 9 In the most recent decade, the changing diet and aging of the global population, coupled with the emergence of diabetes, malignant tumors, and multidrug resistant highly virulent pathogens, account, at least in part, for the annual increase in incidence and mortality rate of PLAs.…”
Section: Introductionmentioning
confidence: 99%
“…Pyogenic LA (PLAs) account for >80% of LA morbidity. The incidence of PLA is higher in Asia compared to Europe and the United States, with an annual incidence of 1.1−5.4/100,000 in China 3,4 and up to 17.6/100,000 in Taiwan, and 1.0−4.1/100,000 in European countries and America 5–7 . Due to the rapid advances in medical technology, the diagnosis and treatment of PLA have greatly improved, resulting in a decrease in mortality rates from >80% at the beginning of the previous century to <10% 8,9 .…”
Section: Introductionmentioning
confidence: 99%